2023
DOI: 10.1021/acsomega.2c07232
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cell Proliferation and Wound Healing Effects of Vitamin A Palmitate-Loaded PLGA/Chitosan-Coated PLGA Nanoparticles: Preparation, Characterization, Release, and Release Kinetics

Abstract: In this study, vitamin A palmitate (VAP)-loaded poly(lactic-co-glycolic acid) (PLGA)/chitosan-coated PLGA nanoparticle (NP) systems were prepared by the nanoprecipitation technique. The prepared systems were characterized by parameters such as particle size, polydispersity index (PDI), ζ-potential, encapsulation efficiency, in vitro dissolution, and release kinetic study. Then, the cytotoxicity and wound healing profiles of the designed NP formulations in HaCaT (human keratinocyte skin cell lines) were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…perforatum oil-doped poly (ϵ-caprolactone)/gelatin nanofibers and observed that HPO loading was a better alternative for diabetic wounds than aloe vera . However, VAP has a dose-dependent wound healing activity . Although, the cell proliferation of the Gt–TA–HPO–VAP nanofiber mat is in an acceptable range, it can be said that an optimization study might be carried out to increase the cell proliferation of the nanofiber mats by changing the VAP amount.…”
Section: Resultsmentioning
confidence: 99%
“…perforatum oil-doped poly (ϵ-caprolactone)/gelatin nanofibers and observed that HPO loading was a better alternative for diabetic wounds than aloe vera . However, VAP has a dose-dependent wound healing activity . Although, the cell proliferation of the Gt–TA–HPO–VAP nanofiber mat is in an acceptable range, it can be said that an optimization study might be carried out to increase the cell proliferation of the nanofiber mats by changing the VAP amount.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, current studies are increasingly focusing on different formulations to reduce drug irritation and improve drug stability, such as combining with other therapeutics to attenuate irritation or to obtain synergistic effects [32][33][34][35][36] Additionally, certain encapsulation carriers were tested to deliver retinoids more efficiently. For example, liposomes 37,38 and other nano-scale carriers 39,40 have been widely used in the retinoid cosmetics industry.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan-coated poly­(lactic- co -glycolic acid) (PLGA/CS) nanoparticles (NPs) are widely employed for drug delivery applications because of their high biocompatibility and sustained release properties. PLGA/CS NPs can encapsulate a variety of cargo, such as vitamins, corticosteroids, anticancer agents, , and phytochemicals . Positive charges on chitosan provide a mucoadhesive effect, increase cellular internalization, and enhance anticancer efficacy.…”
Section: Introductionmentioning
confidence: 99%